Linda C. Hults, The Witch as Muse: Art, Gender, and Power in Early Modern Europe - Clifton, Chas S (Pomegranate, 2007)
Linda C. Hults, The Witch as Muse: Art, Gender, and Power in Early Modern Europe (Philadelphia: University of Pennsylvania Press, 2005), 352 pp., 49.95 (cloth).